2006
DOI: 10.1007/s10886-006-9116-x
|View full text |Cite
|
Sign up to set email alerts
|

Palatability of Macroalgae that Use Different Types of Chemical Defenses

Abstract: This study compared algal palatability and chemical defenses from subtropical green algae that may use different types of defense systems that deter feeding by the rockboring sea urchin Echinometra lucunter. The potential defense systems present include (1) the terpenoid caulerpenyne and its activated products from Caulerpa spp., and (2) dimethylsulfoniopropionate (DMSP)-related defenses in Ulva spp. Secondary metabolites from these chemical groups have been shown to deter feeding by various marine herbivores,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(49 citation statements)
references
References 44 publications
0
49
0
Order By: Relevance
“…are generally unpalatable to fish and invertebrates (Erickson et al 2006). Although some fishes and invertebrates assimilate carbon derived from Caulerpa spp.…”
Section: Discussionmentioning
confidence: 99%
“…are generally unpalatable to fish and invertebrates (Erickson et al 2006). Although some fishes and invertebrates assimilate carbon derived from Caulerpa spp.…”
Section: Discussionmentioning
confidence: 99%
“…In one of the first studies to examine the chemical defenses of marine algal natural products, McConnell et al (1982) showed that caulerpenyne deterred feeding by the sea urchin Lytechinus variegatus. Erickson et al (2006) demonstrated that the subtropical sea urchin Echinometra lucunter was deterred by relatively high concentrations of caulerpenyne (4% dry mass).…”
Section: Caulerpenynementioning
confidence: 99%
“…We collected and cleaned epiphytes from 4 species of macroalgae that have a range of chemical defenses as shown in previous research (Dictyota dichotoma: Ce tru lo & Hay 2000, Wiesemeier et al 2007; Caulerpa sertularioides : Paul & Fenical 1986, Erickson et al 2006Sargassum polyceratium: Boettcher & Targett 1993, Thabard et al 2011Turbinaria turbinata: Meyer et al 1994, Stiger et al 2004, and a nonchemically defended species of algae (Acanthophora spicifera: Fong et al 2006). We weighed 5.0 ± 0.1 g (mean ± SE) samples of each alga after drying in a salad spinner for 1 min, and cable-tied a sample of each alga to each experimental unit, which were rocks collected from each site and covered with wire mesh to facilitate attachment.…”
Section: Methodsmentioning
confidence: 99%
“…resource availability and herbivory rates) may also cause variation in nutritional quality of coral reef algae, controlling the ability of producers to alter their palatability and reduce their consumption by herbivores (e.g. Erickson et al 2006). It is argued that when resources are low, primary producers that grow slowly and invest more in antiherbivore defense are favored, and that the opposite is also true (i.e.…”
Section: Introductionmentioning
confidence: 99%